Disturbed small-world networks and neurocognitive function in frontal lobe low-grade glioma patients. - Qingling Huang; Rui Zhang; Xinhua Hu; Shangwen Ding; Jingguang Qian; Ting Lei; Xuan Cao; Ling Tao; Zhiyu Qian; Hongyi Liu (PLoS ONE)
Background Brain tumor patients often associated with losses of the small-world configuration and neurocognitive functions before operations. However, few studies were performed on the impairments of frontal lobe low-grade gliomas (LGG) after tumor resection using small-world network features. Methodology/principal findings To detect differences in the whole brain topology among LGG patients before and after operation, a combined study of neurocognitive assessment and graph theoretical network analysis of fMRI data was performed. We collected resting-state fMRI data of 12 carefully selected frontal lobe LGG patients before and after operation. We calculated the topological properties of brain functional networks in the 12 LGG, and compared with 12 healthy controls (HCs). We also applied Montreal Cognitive Assessment (MoCA) in a subset of patients (n = 12, including before and after operation groups) and HCs (n = 12). The resulting functional connectivity matrices were constructed for all 12 patients, and binary network analysis was performed. In the range of 0.05 ≤ Kcos t ≤ 0.35, the functional networks in preoperative LGG and postoperative one both fitted the definition of small-worldness. We proposed Knet = 0.20 as small-world network interval, and the results showed that the topological properties were found to be disrupted in the two LGG groups, meanwhile the global efficiency increased and the local efficiency decreased. Lnet in the two LGG groups both were longer than HCs. Cnet in the LGG groups were smaller than HCs. Compared with the Hcs, MoCA in the two LGG groups were lower than HCs with significant difference, and the disturbed networks in the LGG were negatively related to worse MoCA scores. Conclusions Disturbed small-worldness preperty in the two LGG groups was found and widely spread in the strength and spatial organization of brain networks, and the alterated small-world network may be responsible for cognitive dysfunction in frontal lobe LGG patients.